Strategi Pembelajaran Sejarah Kebudayaan Islam melalui Storytelling dan Media Digital untuk Meningkatkan Minat dan Pemahaman Siswa di SDIT Al-Furqon Karawang - Ayu Desy Hidayah; Azizah Farahdilah; Annisa Tazkia; Devika Rindani; Afiyatun Kholifah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to explore ways of teaching Islamic Cultural History (SKI) to increase students' interest and understanding through the implementation of storytelling methods and the use of digital media at SDIT MTA Al-Furqon Karawang. The method used in this study is a descriptive qualitative approach, with SKI teachers as the main informants. The data collection process was carried out through observation, semi-structured interviews, and documentation studies. The findings of this study indicate that the storytelling method can enhance students' focus, enthusiasm, and understanding of Islamic history material, because the delivery of interesting and relevant stories helps students comprehend the course of events and the moral values contained within them. In addition, the use of digital media such as educational videos, YouTube, podcasts, and other audiovisual media supports students' understanding in a more visual and interactive way, as well as in accordance with the characteristics of students in today's digital era. Teachers also integrate teaching methods with discussions, educational games, role-playing, and drama to increase student engagement. Although there are some challenges such as the low interest of some students, difficulty in remembering historical material, and time constraints in the learning process, the strategies implemented have been proven capable of creating an active, enjoyable, and meaningful learning environment. Thus, the use of storytelling methods and digital media has been proven effective in improving the quality of SKI teaching as well as instilling moral values and student character.